(untitled) (Geology of the Intermountain West, 2023)
The multiple origins proposed for the Kanarra anticline in southwestern Utah as a drag-fold along the Hurricane fault, a Laramide monocline, a Sevier fault-propagation fold, or a combination of these processes, serve to muddy its tectonic significance. This in part reflects the structural complexity of the exposed eastern half of the fold. The fold evolved from open and up-right to overturned and tight, is cross-cut by multiple faults, and was subsequently dismembered by the Hurricane fault. The western half of the fold is obscured because of burial, along with the hanging wall of the Hurricane fault, beneath Neogene and younger sediments and volcanics. We present the results of detailed bedrock geologic mapping, and geologic cross sections restored to Late Cretaceous time (prior to Basin and Range extension), to demonstrate the Kanarra anticline is a compound anticline-syncline pair inextricably linked with concomitant thrust faulting that formed during the Sevier orogeny. We propose the name Kanarra fold-thrust structure to unambiguously identify the close spatial and temporal association of folding and thrusting in formation of this prominent geologic feature. We identify a previously unrecognized thrust, the Red Rock Trail thrust, as a forelimb shear thrust that was in a favorable orientation and position to have been soft-linked, and locally hard-linked, with the thrust ramp of the basal detachment to form a break thrust. The east verging Red Rock Trail thrust is recognized by a distinctive cataclasite in the Lower Jurassic Navajo Sandstone. The hanging wall of the Red Rock Trail thrust is displaced eastward over the Middle Jurassic Carmel Formation and Upper Cretaceous formations and can be traced for at least 27 km and possibly farther. We contend the Kanarra fold-thrust structure unambiguously defines the leading edge of the Sevier fold-thrust belt in southwestern Utah. Stratigraphic relationships in the southern and northern part of the Kanarra fold-thrust structure constrain its development between the early and late Campanian (about 84 to 71 Ma) but possibly younger. In southwestern Utah, initial movement along the Iron Springs thrust at about 100 Ma (Quick and others, 2020) and subsequent eastward advancement of the Sevier deformation front to the Red Rock Trail thrust at about 84 to 71 Ma coincided with well-documented magmatic flare ups in the Cordilleran arc in the hinterland of the Sevier fold-thrust belt. This temporal relationship between magmatic flare ups and thrusting is consistent with a close correspondence between arc-related processes and episodic foreland deformation.